The relationships between soil compaction and soil physical-chemical-biological characteristics: A case study from volcanic agricultural soils of Entisol and Ultisol in North Maluku Province of Indonesia - Ishak, Lily; Teapon, Amiruddin; Hindersah, Reginawanti; Nurmayulis, Nurmayulis; Erwin, Erwin; Hartati, Tri Mulya (Journal of Degraded and Mining Lands Management, 2024)
Soil compaction has been recognized as a form of soil degradation that mostly deteriorates agricultural soil health worldwide from various climatic conditions and soil management. Heavy compaction can occur in agricultural soils due to intensive tillage, where its effects on soil properties have been the focus of many studies. The present study was undertaken to assess whether soil compaction occurs in agricultural soils adopting no-tillage systems and how the link between soil compaction and chemical-biological characteristics could be. A field investigation was carried out in two different locations that have different soil types, Entisol in Maitara Island and Ultisol in Halmahera Island, North Maluku Province. Sixteen undisturbed and disturbed soil samples were collected from each location grown with cassava and taken to the laboratory for analysis. Soil components observed included soil texture, bulk density, particle density, total porosity, soil permeability, soil organic matter (SOM), total nitrogen (N), phosphorous (P) availability, and phosphate-solubilizing bacteria (PSB). The findings revealed linear relationships between soil compaction and sand fraction, SOM, PSB, and available P, but none were found in soil total N. These results confirmed the importance of soil compaction management in food crop agricultural systems, particularly when soil carbon is low, to promote soil health. As the inconsistent correlation of soil compaction and chemical-biological properties was found in these two soil types, further investigation is necessary.